ECONOMIC ANALYSIS IN VEGETABLE SECTOR OF ROMANIA - Elena SOARE; Iuliana DOBRE; Livia DAVID (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper emphasizes the main tendency in the vegetables field of Romania by examining economic indicators. The aim is to find the ability of the Romanian market to provide the necessary with vegetables. In order to answer to the question was analyzed total area, total production, average production, average prices, average consumption, import and export. The analysis was made for the period 2011-2015. The obtained results show a diminishing of indicators.